Trisurethane functionalized sulfonamide based polymeric sorbent: Synthesis, surface properties and efficient mercury sorption from wastewater - Akgul, Ebru Tekneci; Isik, Birol; Senkal, Bahire Filiz; Cankurtaran, Ozlem (ELSEVIER, 2023)
In this study, trisurethane modified sulfonamide based polymeric adsorbent was prepared starting from reaction with chlorosulfonated poly (styrene) (PS) beads and tris(hidroxymethyl) aminometane. Hydroxyl functions of the adsorbent were reacted with butyl isocyanate in the presence of dibutyltin dilaurate as a catalyst at 60 0C for 48 h to obtain tris urethane functional polymeric adsorbent (PS-TUR). Spectroscopic and morphological characterizations of the polymeric adsorbents were carried out using scanning electron microscopy (SEM-EDX), infrared spectrophotometry (FTIR), XPS and analytical methods. The surface properties of PS-TUR were investigated for the first time with the inverse gas chromatography technique at infinite dilution before adsorption studies.The dispersive surface energy of adsorbent was determined according to the method of Schultz (55.54-61.73 mJ m-2) and Dorris-Gray (57.70-67.03 mJ m-2). Adsorption enthalpy and Gibbs free energy were calculated according to this technique and it was determined that the adsorption was exothermic and spontaneous. As a result of the analyzes made with this technique, it was determined that the PS-TUR adsorbent surface was acidic (KD/KA = 0.27 < 1) and optimum conditions (pH: 7, dose: 0.10 g) were determined for the effective adsorption of Hg (II) ions. Surface acidity-basicity behavior of sorbent was determined by isoelectric point (IEP: 6.20) and pHpzc (5.81) analyses.Batch adsorption studies of the PS-TUR adsorbent were carried out as a function of adsorbent dosage, pH, initial metal ion concentration (0.0025-0.1000 mol/L), and kinetically. After determination of optimum adsorbent dosage was found as 100 mg, mercury sorption capacity of PS-TUR adsorbent was found as 511.50 mg g-1 adsorbent.Desorption studies were carried out using glacial acetic acid and studies demonstrated that PS-TUR adsorbent is regenerable and can be successfully used for four adsorption-desorption cycles without significant loss its capacity.Also, PS-TUR adsorbent shows selectivity with high sorption capacity towards mercury as compared to other metal ions.
Keywords: Sulfonamide; Mercury removal; Urethane; Inverse gas chromatography; Surface properties; HEAVY-METAL IONS; AQUEOUS-SOLUTION; CARBON NANOTUBES; CONTACT-ANGLE; ADSORPTION; REMOVAL; EQUILIBRIUM; RESIN; ACID; CELLULOSE; Engineering